Usability Analysis on the OPAC UNSIKA Website Using the User Centered Design Method - Naibaho, Syela Herdina; Sulistiyowati, Nina; Siska, Siska (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 3 (2025): JELIKU Volume 13 No 3, February 2025DO - 10.24843/JLK.2025.v13.i03.p06, 2025)
Online Public Access Catalog (OPAC) is a key service for students and faculty to search, access, and manage library collections. However, usability issues have led to complaints, highlighting the need for evaluation. The User-Centered Design (UCD) method was chosen for its focus on user needs in system development. This study aims to improve the website's usability in effectiveness, efficiency, and user satisfaction. Key issues identified include unattractive design, confusing navigation, excessive menu options, and an ineffective search feature. The research followed UCD stages: specifying the context of use, identifying user requirements, creating design solutions, and evaluating them. Added features include a member list, book collections, and a help desk. Results showed a 34.1% increase in effectiveness, a 15-second improvement in efficiency, and a rise in the SUS score to 79, making the website more user-friendly